A Transient‐Directing‐Group Strategy Enables Enantioselective Reductive Heck Hydroarylation of Alkenes. (7th April 2020) - Oxtoby, Lucas J.; Li, Zi‐Qi; Tran, Van T.; Erbay, Tuğçe G.; Deng, Ruohan; Liu, Peng; Engle, Keary M.
Abstract: Metal‐coordinating directing groups have seen extensive use in the field of transition‐metal‐catalyzed alkene functionalization; however, their waste‐generating installation and removal steps limit the efficiency and practicality of reactions that rely on their use. Inspired by developments in asymmetric organocatalysis, where reactions rely on reversible covalent interactions between an organic substrate and a chiral mediator, we have developed a transient‐directing‐group approach to reductive Heck hydroarylation of alkenyl benzaldehyde substrates that proceeds under mild conditions. Highly stereoselective migratory insertion is facilitated by in situ formation of an imine from catalytic amounts of a commercially available amino acid additive. Computational studies reveal an unusual mode of enantioinduction by the remote chiral center in the transient directing group. Abstract : You come and go : A commercially available chiral transient directing group (l ‐ tert ‐leucine) facilitates the enantioselective reductive‐Heck hydroarylation of internal styrene substrates. This operationally simple reaction shows high functional‐group tolerance and generates enantioenriched 1, 2‐diaryl ethane motifs in synthetically useful yields under mild conditions.